EFFECT OF PROBIOTIC BACILLUS SUBTILIS STRAIN BR2CL AND BACILLUS SP. STRAIN BT3CL STRAIN THROUGH DRINKING WATER AGAINST ORGANOLEPTIC BALI DUCK MEAT GIVEN RATIONS CONTAINING GREEN BEAN SPROUTS SKIN FLOUR - F., Bongi; Siti, N.W.; Candrawati, D.P.M.A (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to determine the effect of a mixture of probiotic Bacillus sp. strains BT3CL and Bacillus subtilis strain BR2CL through drinking water against Bali ducks organoleptics which were given rations containing mung bean sprouts skin flour.  The design used was a completely randomized design (CRD) consisting of 3 treatments and 5 replications. The treatments given were A (ducks without being given probiotics through drinking water); B (ducks given a mixture of probiotic Bacillus sp. Strain BT3CL and Bacillus subtilis strain BR2CL through drinking water as much as 2.5 ml); C (ducks given a mixture of probiotic Bacillus subtilis strain BR2CL and Bacillus subtilis strain BR2CL through drinking water as much as 5 ml). The variables observed included color, aroma, taste, texture, and overall acceptance. The results showed that the probiotic mixture of Bacillus sp. strains BT3CL and Bacillus subtilis strain BR2CL had no significant effect (P> 0.05) on organoleptic Bali duck meat. Based on the results of the study, it can be concluded that the probiotic mixture of Bacillus subtilis strains BR2CL and Bacillus sp. BT3CL strain through drinking water at 5 ml / head / day treatment, did not affect the organoleptic quality of female bali duck meat.   Key words: organoleptic, probiotic, duck meat.